(untitled) (Nepalese Journal of Management Research, 2024)
The Bharatpur coffee business has expanded significantly, drawing a wave of youthful entrepreneurs keen to take advantage of the growing consumer demand for coffee experiences and goods. In order to promote sustainable company development and economic prosperity, this dynamic market necessitates a thorough investigation of the critical elements influencing entrepreneurial growth.This study looks into how important variables including market trends, social engagement, and economic stability interact with entrepreneurial success. It uses a thorough technique, which includes a pilot research, to gather and examine information from 35 local coffee shops. Significant correlations and regression coefficients between economic factors, market trends, social factors, and entrepreneurial growth are revealed by the data. Notably, growth and stability in the economy are recognized as important factors that have a big influence on how well businesses operate. Conversely, it is discovered that actively tracking rivals has less of an effect on competitiveness.This study makes recommendations for policymakers and coffee entrepreneurs to improve the expansion and sustainability of coffee enterprises in Bharatpur based on its results. These suggestions cover a wide range of topics, including developing strategic alliances and customizing goods and services to match current market trends. As a result, they provide practical advice for anyone involved in the coffee industry.This study advances our knowledge of the variables influencing entrepreneurial growth within the framework of Bharatpur’s coffee industry. For local business owners, industry participants, and legislators looking to promote economic expansion and entrepreneurial success in the area, it is an invaluable resource.